2015
DOI: 10.1002/chem.201500644
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism Leading to Formation of the Cysteine Sulfinate Product Complex of a Biomimetic Cysteine Dioxygenase Model

Abstract: Cysteine dioxygenase is a unique nonheme iron enzyme that is involved in the metabolism of cysteine in the body. It contains an iron active site with an unusual 3-His ligation to the protein, which contrasts with the structural features of common nonheme iron dioxygenases. Recently, some of us reported a truly biomimetic model for this enzyme, namely a trispyrazolylborato iron(II) cysteinato complex, which not only has a structure very similar to the enzyme-substrate complex but also represents a functional mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 81 publications
2
42
0
Order By: Relevance
“…However, we also considered the possibility that the S = 1 Fe/O 2 adduct consists of a low-spin Fe(III) ion ferromagnetically coupled to O 2 •− , as this configuration yielded the lowest-energy Fe/O 2 model in de Visser’s study of complex 3 . 39 The resulting computational models are labeled spin [ 2-O 2 ] (HS,LS) and spin [ 4-O 2 ] (HS,LS) , where HS and LS indicate whether the Fe center is high-spin or low-spin, respectively. Metric parameters of the geometry-optimized structures are provided in the Supporting Information (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we also considered the possibility that the S = 1 Fe/O 2 adduct consists of a low-spin Fe(III) ion ferromagnetically coupled to O 2 •− , as this configuration yielded the lowest-energy Fe/O 2 model in de Visser’s study of complex 3 . 39 The resulting computational models are labeled spin [ 2-O 2 ] (HS,LS) and spin [ 4-O 2 ] (HS,LS) , where HS and LS indicate whether the Fe center is high-spin or low-spin, respectively. Metric parameters of the geometry-optimized structures are provided in the Supporting Information (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Metric parameters of the geometry-optimized structures are provided in the Supporting Information (Table S3). Whereas de Visser found that O 2 binding to 3 triggers dissociation of a pyrazole donor regardless of spin state, 39 nearly allo of our optimized Fe/O 2 models are 6C with Fe-N TIP/Tp bonds lengths ≤ 2.31 Å; the only exceptions being the S =3 [ 2-O 2 ] HS and S =2 [ 2-O 2 ] HS models, in which one of the Fe-N TIP bonds elongates to ~2.4 Å during geometry optimization to yield quasi-6C structures (Table S3). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical analysis could rationalize that the reaction of 10 with O 2 is comparatively slow: O 2 binding was found to be endergonic and thus represents the rate-determining step. 21 An independent theoretical work (using similar methods) published very recently arrived at similar conclusions, although specific energies and structures varied somewhat. 22 In 2012, Goldberg et al presented a further iron(II) thiolate complex that reacted with O 2 via dioxygenation at the S atom.…”
Section: B Model Systemsmentioning
confidence: 70%
“…An extensive set of computational studies on CDO enzymes 35 -37 and model complexes was performed. 38,39 The calculations showed that the 3-His ligand system in CDO is essential for complete dioxygenase activity and significant amount of cysteine sulfoxide product is predicted in CDO with a 2-His/1-Asp ligand system. Furthermore, the ligand environment is important for spin state ordering and catalysis.…”
Section: Introductionmentioning
confidence: 99%